Purification of ethanol for highly sensitive self-assembly experiments - Barbe, Kathrin; Kind, Martin; Pfeiffer, Christian; Terfort, Andreas (Beilstein Journal of Nanotechnology, 2014)
Ethanol is the preferred solvent for the formation of self-assembled monolayers (SAMs) of thiolates on gold. By applying a thin film sensor system, we could demonstrate that even the best commercial qualities of ethanol contain surface-active contaminants, which can compete with the desired thiolates for surface sites. Here we present that gold nanoparticles deposited onto zeolite X can be used to remove these contaminants by chemisorption. This nanoparticle-impregnated zeolite does not only show high capacities for surface-active contaminants, such as thiols, but can be fully regenerated via a simple pyrolysis protocol.
Keywords: ethanol; gold nanoparticles; purification; self-assembled monolayers; solvent